The Implementation of the Small Group Discussion Learning Model on the Learning Outcomes of Fifth Grade Students in the Pancasila Education Subject at SD Negeri Seilale - Pormes, Enny Abigael; Titus Gaite; Nathalia Y Johannes (The Future of Education Journal, 2025)
Small Group Discussion is a learning model that involves two or more individuals interacting intensively and face-to-face to achieve predetermined goals through the exchange of information, opinions, or problem-solving. Learning outcomes include students’ ability to develop metacognitive skills, such as their capacity to plan, organize, and evaluate their own learning processes. These outcomes are often linked to students’ engagement in the learning process. The method used in this research is Classroom Action Research (CAR). CAR is a problem-solving process that applies scientific methods involving collaboration and cooperation between researchers, educators, and participants. It is a specific variant of action research that plays a significant and strategic role in improving the quality of teaching and learning activities. The results of this study indicate that students are able to interact intensively and face-to-face in identifying and solving problems, exploring or debating issues, which is considered effective in stimulating thinking, challenging attitudes and beliefs, and developing students’ interpersonal skills. Students are also able to share knowledge, experiences, and perspectives with their group members. Furthermore, they are capable of giving and receiving feedback, asking questions, presenting arguments, and concluding the results of discussions. Overall, the implementation of the Small Group Discussion model proves to be effective in improving student learning outcomes.